Assessing the efficiency of floor disinfection on bacterial decontamination in sanandaj governmental hospitals - Shadi Kohzadi; Rashid Ramazanzade; Hozan Loqmani; Pegah Shakib; Hamed Ghaderzadeh; Bita Khasi; Naser Reshadmanesh (Journal of Advances in Environmental Health Research, 2018)
Despite regular disinfection and decontamination of the hospital floors and surfaces, resistant pathogens from the hospital surfaces and their transmission to humans have been reported recently. The resistance of pathogens to the disinfectant agents or failed disinfection techniques have put the routine floor and non-critical surface disinfection done in hospitals into question with regard to their effectiveness. In this study, 112 samples were collected using cotton swabs which were immediately placed in a broth agar media. The collected samples were cultured in broth agar and eosin methylene blue media. We determined the bacterial load on the ward floors and patient rooms before and after disinfection and assessed the effectiveness of the used method and decontamination agents in cleaning the floors. The results showed that disinfection did not have a significant effect on the hospital surface decontamination, and the disinfection process did not change the colony count in the different wards of the hospital (P-value < 0.05).